Engines of Liberation - Greenwood, Jeremy; Seshadri, Ananth; Yorukoglu, Mehmet (Review of Economic Studies, 2005)
Electricity was born at the dawn of the last century. Households were inundated with a ood of new consumer durables. What was the impact of this consumer durable goods revolution? It is argued here that the consumer goods revolution was conducive to liberating women from the home. To analyze this hypothesis, a Beckerian model of household production is developed. Households must decide whether or not to adopt the new technologies, and whether a married woman should work. Can such a model help to explain the rise in married female labor-force participation that occurred in the last century? Yes.